Artificial Intelligent: Positive And Negative Role in Education Management - Suharyat, Yayat; Lusiana (Proceeding International Conference on Education, 2023)
Technology always has positive and negative effects. To minimize unwanted effects, work around this. The research aims to explore AI's positive and negative roles in Education management. The data collection technique is a literature study. Data analysis was carried out by identifying the benefits of AI in Education and its impact on the quality of education. The study results show that AI has a positive role in education management, such as presenting a more innovative learning process and speed in organizing and managing learning activities and increasing the quantity and quality of lecturers' scientific work. However, AI harms social interaction between pupils and teachers. It can potentially imprison the learning community (lecturers, teachers, students) in a state of convenience, undermining the critical thinking innovation it should have had thus far. This study found that AI improves schooling. It must be maintained to maintain learning citizens' social interaction and inventive thinking.